Synthesis of Multicriteria Controller by Means of Fuzzy Logic Approach - Andrew Lozynskyy; Lyubomyr Demkiv (Advances in Fuzzy Systems)
A two-mass fuzzy control system is considered. For fuzzification process, classical both linear and nonlinear membership functions are used. To find optimal values of membership function’s parameters, genetic algorithm is used. To take into account values of both output and intermediate parameters of the system, a penalty function is considered. Research is conducted for the case of speed control system and displacement control system. Obtained results are compared with the case of the system with classical, crisp controller.